2021
DOI: 10.1093/fampra/cmab168
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for incidence of dementia in primary care practice: a retrospective cohort study in older adults

Abstract: Background The dementias are long-term, chronic conditions caused by progressive neurological degeneration. Current literature suggests that cardiovascular disease risk factors may contribute to the onset of dementia; however, evidence of these associations is inconsistent. Objectives This study aimed to examine the impact of risk factors on dementia onset in older adults diagnosed and managed in Canadian primary care setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…30 Conversely, another study determined that both malignant melanoma and non-melanoma skin cancers were associated with a decreased ADRD risk, suggesting a protective effect. 60 Kidney disease, 21, 51 hip fracture, 46 and osteoarthritis 54 were also identified as risk factors for ADRD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Conversely, another study determined that both malignant melanoma and non-melanoma skin cancers were associated with a decreased ADRD risk, suggesting a protective effect. 60 Kidney disease, 21, 51 hip fracture, 46 and osteoarthritis 54 were also identified as risk factors for ADRD.…”
Section: Resultsmentioning
confidence: 99%
“…Both smoking 54 and alcohol use– as determined by overall consumption and alcohol-induced loss of consciousness 56 – were identified as risk factors for ADRD. Conversely, a healthy lifestyle, characterized by no current smoking, moderate alcohol consumption, regular physical activity, healthy diet, adequate sleep duration, less sedentary behavior, and frequent social contact, exhibited a protective effect against ADRD in patients with type II diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another cohort study of 245,483 participants showed that older adults with multiple comorbid conditions had a higher risk of dementia [ 26 ]. Other factors reported as being relevant include aging, polypharmacy, and a heavier treatment burden, all of which might affect the brain and cause neural injuries [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%